Answer:
h = 2
k = 5
Explanation:
Midpoint between two points
![\textsf{Midpoint}=\left((x_2+x_1)/(2),(y_2+y_1)/(2)\right)\quad \textsf{where}\:(x_1,y_1)\:\textsf{and}\:(x_2,y_2)\:\textsf{are the endpoints}}\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/9y1nys74dh8ezts4dzt7rez483wbqmw8lk.png)
Given:
- B = Midpoint = (6, 0)
- A = (x₁, y₁) = (3h+4, 1-2h)
- C = (x₂, y₂) = (k-3, k-2)
Substitute the given values into the formula:
![\implies (6, 0)=\left((k-3+3h+4)/(2),(k-2+1-2h)/(2)\right)](https://img.qammunity.org/2023/formulas/mathematics/college/ly6iye68kux8pfq7m567z1fg6rkczh5pg3.png)
![\implies (6, 0)=\left((k+3h+1)/(2),(k-2h-1)/(2)\right)](https://img.qammunity.org/2023/formulas/mathematics/college/umn24e212zl0ynkk9z1vpzv5ltyc70lxp3.png)
Equating the x-values to create an expression for k:
![\implies (k+3h+1)/(2)=6](https://img.qammunity.org/2023/formulas/mathematics/college/vmqmpm8xqyeisupwys7p7u5c8qqixbb62g.png)
![\implies k+3h+1=12](https://img.qammunity.org/2023/formulas/mathematics/college/dwl1tf0sdwro6h8ykqdzdcplbd1gt3z3ow.png)
![\implies k+3h=11](https://img.qammunity.org/2023/formulas/mathematics/college/vgdecu23nct3ksysznkm0l9y56zxzbnwyc.png)
![\implies k=11-3h](https://img.qammunity.org/2023/formulas/mathematics/college/h32ygedngxa1q0tv6cr8qh9o4nsakvf1r2.png)
Equating the y-values to create an expression for k:
![\implies (k-2h-1)/(2)=0](https://img.qammunity.org/2023/formulas/mathematics/college/epeghvfa5lm7ruh5woqa2t46lb5e3tydff.png)
![\implies k-2h-1=0](https://img.qammunity.org/2023/formulas/mathematics/college/kx0to69qp61n6vgz4wyxe6310pw7wg40fm.png)
![\implies k-2h=1](https://img.qammunity.org/2023/formulas/mathematics/college/puqh9zdiwfp14ugx2t5b0a0m5he504bijq.png)
![\implies k=2h+1](https://img.qammunity.org/2023/formulas/mathematics/college/o684a7ydu0fub84vv7s0rp65ijskeo5w7u.png)
Equate the expressions for k and solve for h:
![\implies 2h+1=11-3h](https://img.qammunity.org/2023/formulas/mathematics/college/n4jqzmbs29zmnxu6mer4lk8aj6lek9h8ma.png)
![\implies 5h=10](https://img.qammunity.org/2023/formulas/mathematics/college/heyey4h3k0uduk8bgj99ne8zq2o3fri9s2.png)
![\implies h=2](https://img.qammunity.org/2023/formulas/mathematics/college/yvn5963bn49mi1ji6m28j1g5ybfw9ri5gb.png)
Substitute the found value of h into one of the equations for k and solve for k:
![\implies k=2(2)+1](https://img.qammunity.org/2023/formulas/mathematics/college/e6q4a6mjygvow2i8mg8z8bmgfw4zztzxbx.png)
![\implies k=4+1](https://img.qammunity.org/2023/formulas/mathematics/college/d9t85ljz4tuvsgratc0gld1zw9xwazhjio.png)
![\implies k=5](https://img.qammunity.org/2023/formulas/mathematics/college/374r46h5wckwwazerggic7y6aseq5ggcgs.png)